Illapu in exile and its (pop) Andean paths - Jordán González, Laura (Revista de Historia Social y de las Mentalidades, 2025)
This article studies part of Illapu's history in exile, inquiring into the stylistic transformation and production of discourses informed by the transnational experience. In particular, I interrogate the strategies Illapu takes to update the place of "the Andean" in their music. On the one hand, it stresses the exploration of pop and Afro-Latin sonorities is addressed, through the incorporation of the electric bass and new rhythms. On the other hand, the production of self-promotional discourses in international tours is examined, observing the relativization of the political component and a reinvigoration of the Andean in the eyes of diverse audiences, where the reinvention of the local becomes crucial.
Keywords: Andean music, exile, music style